Penerapan Analisis Algoritma Elias Omega Code Pada Citra Digital - Liskedame Yanti; Sinaga, Chaston Ramotto; Sagala, Angelica Claudia (UNIKA Santo Thomas, 2024)
The large size of digital image files is an obstacle in their storage, transmission, and processing. Digital image compression is a solution to overcome this problem. The Elias Omega Code algorithm is one of the efficient and easy-to-implement lossless compression algorithms. This research aims to analyze the Elias Omega Code algorithm on digital images. The analysis includes: implementation of the Elias Omega Code algorithm for digital image compression, evaluation of the performance of the Elias Omega Code algorithm in terms of compression ratio and image quality, comparison of the performance of the Elias Omega Code algorithm with other image compression algorithms. The results of the study show that the Elias Omega Code algorithm can produce a high compression ratio with preserved image quality. This algorithm has better performance than the Huffman and LZW algorithms, but lower than the JPEG algorithm..